This sky, over everything - Nelson, Cherie, author; Candelaria Fletcher, Harrison, advisor; Thompson, Deborah, committee member; MacDonald, Bradley, committee member (Colorado State University. Libraries, 2019)
"This Sky, Over Everything," is a collection of creative nonfiction essays that circle around grief and the aftermath of loss. Using the over-arching metaphors of constellation, navigation, and sacred texts, the eleven pieces within this collection focus on the narrator's loss of a childlike faith system as well as the relationships and certainty this system provided. Through braided, collage, and mosaic essays, as well as flash nonfiction, the collection moves toward renegotiation as the narrator attempts to navigate the word, her faith, and relationships with others.